Xayrulla THE SEMANTICS OF THE AFFIXES AND THEIR COMPARATIVE ANALYSIS: THE SEMANTICS OF THE AFFIXES AND THEIR COMPARATIVE ANALYSIS - Jumanazarov, Khayrulla (Журнал иностранных языков и лингвистики, 2022)
The aim of comparative analysis to single out, describe, compare and find the possible ways of classification of English affixes. The scientific interest of this work can be the following: we will familiarize ourselves with English affixes, learn how they differ semantically from each other, which affixes are used with stems of different parts of speech and what parts of speech they form , what their functions and peculiarities of usage are, and which affixes are more productive and widely used nowadays. It is very important to know as more affixes, as possible, because many English words are formed by combining prefixes and suffixes to base words. The more prefixes and suffixes we know, the easier it will be for us to figure out the meanings of these words .